2001
DOI: 10.1097/00005650-200112000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy, Depressive Symptoms, and Patients’ Expectations Predict Outcomes in Asthma

Abstract: Less asthma self-efficacy, more depressive symptoms, and unrealistic expectations predict worse asthma outcomes. These relatively unexplored patient-centered variables in asthma are potentially modifiable and may offer new ways to intervene to improve asthma outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
102
2
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 52 publications
12
102
2
4
Order By: Relevance
“…After adjusting for some confounding factors such as age, sex, and race of the participants, glucocorticoid use, and prior exacerbations, the heterogeneity among the studies was reduced (21,22,25). Substantial heterogeneity also existed in the outcome of ED visits because of asthma, and adjustment for confounding factors such as age, sex, race, years of education, smoking, asthma control, inhaled corticosteroid dose, and medication adherence resulted in a significant statistical difference for the relation between PD and ED visits because of asthma (10,12,20,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After adjusting for some confounding factors such as age, sex, and race of the participants, glucocorticoid use, and prior exacerbations, the heterogeneity among the studies was reduced (21,22,25). Substantial heterogeneity also existed in the outcome of ED visits because of asthma, and adjustment for confounding factors such as age, sex, race, years of education, smoking, asthma control, inhaled corticosteroid dose, and medication adherence resulted in a significant statistical difference for the relation between PD and ED visits because of asthma (10,12,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Ten of these were eligible prospective cohort studies and were included in the analysis (10)(11)(12)(20)(21)(22)(23)(24)(25)(26). The flowchart for screening studies is shown in Figure 1.…”
Section: Characteristics and Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in asthma self-management efficacy following exposure to AsthmaWise contradicts current knowledge which links high self-efficacy with better asthma control and asthma related quality of life (60,61). It is possible that this drop in self-management efficacy occurred because, prior to exposure to AsthmaWise, participants were unaware of the seriousness of asthma.…”
Section: Discussionmentioning
confidence: 78%
“…Self-efficacy is a well-documented predictor of treatment outcome and, together with expectancy, has been associated with subjective recovery and adherence to physiotherapy 53 and outcomes such as AQLQ score in people with asthma. 54,55 The items selected were based on Lorig's three-item Exercise Regularly Scale, 56 which was created to assess self-efficacy to perform self-management behaviours in people with chronic disease, correctly, every day and without making their symptoms worse. The three self-efficacy items are rated on a scale from 0 to10.…”
Section: Expectancy (Baseline)mentioning
confidence: 99%